2020
DOI: 10.1177/0042085920914354
|View full text |Cite
|
Sign up to set email alerts
|

Caring and Uncaring Teacher Practices: Examples From Past Offer Guidance for Present and Hope for Future

Abstract: This article employs narrative inquiry to illuminate how teachers’ embodied culture of care, or lack thereof, effects African American students. The majority teacher (young, White, female) often struggles to counter the cultural mismatch and connect with her diverse student population. This study highlights narratives of African American students who attended both segregated and newly integrated schools during the 1950s to 1970s, and offers an exemplar of teacher practices and behaviors that lead to a culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…While a minority of students in our sample reported negative classroom interactions and racial microaggressions, for those who did have these experiences it not only had consequences for students’ academic performance but also indicated to students that their teachers did not care about them. This highlights the critical importance of teachers taking conscious and proactive steps to build authentic, culturally responsive, and caring relationships with Black students (Wandix-White, 2020) – a mantle that has long been taken up by Black educators (McKinney de Royston et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…While a minority of students in our sample reported negative classroom interactions and racial microaggressions, for those who did have these experiences it not only had consequences for students’ academic performance but also indicated to students that their teachers did not care about them. This highlights the critical importance of teachers taking conscious and proactive steps to build authentic, culturally responsive, and caring relationships with Black students (Wandix-White, 2020) – a mantle that has long been taken up by Black educators (McKinney de Royston et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in applying the concept of care to interpret the findings further, there are a number of key insights gained. The collective counter-narrative, with its three overarching themes, reflects all six categorical care behaviors as outlined by Rivera-McCutchen (2012) and all but one of the characteristics associated with a culture of care outlined by Wandix-White (2020); exhibiting a strong community presence was the one culture of care characteristic not gleaned. Though due to limitations with the data collected it cannot be concluded that each teacher did or did not exhibit all six care behaviors or a strong community presence.…”
Section: Discussionmentioning
confidence: 99%
“…This study borrows from Rivera-McCutchen’s (2012) conceptualization of caring as a set of six categorical behaviors, based on a synthesis of relevant literature: the emotional and academic support provided students, the high level of work expected from students, the valuing of parents as resources, understanding the sociocultural and sociopolitical factors that shape students’ educational experiences, the communication of standards, and believing students are capable of academic rigor. The characteristics that African American teachers demonstrated with their Black students to develop a culture of care during the era of segregation align with those offered by Rivera-McCutchen, with the addition of teachers exhibiting a strong community presence, having a concern for students’ futures, and caring for all students (Wandix-White, 2020). Though racial-matching between teachers and students or a lack thereof is not a determinant of teacher caring, a teacher's cultural background does inform their notions of caring and associated practices (Milner, 2006).…”
Section: Conceptual Frameworkmentioning
confidence: 93%
“…Although education systems maintain the gap, every single student can make significant yearly academic progress. Thus, while for me the catalyst was the environmental force created by a determined teacher and a classroom culture of care (Wandix-White, 2020), there is an inherent spark of resilience that exists within every African American student. Finding that spark and creating the right environment to kindle a flame may ignite a slow burn of the systems that perpetuate the gap.…”
mentioning
confidence: 99%